Study of Socio-Economic of Fresh Water Fish Family in Rao Selatan District Pasaman Region - Yanti, Martini; Rianto, Slamet; Farida, Farida (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ This study aimed to obtain the data, process, analyze and discuss the socich-economic conditions of freshwater fish farmers in Rao Selatan district Pasaman Region views of: 1) Income, 2) Basic Need Fulfillment, 3) family education and 4) Family health. This research is a descriptive. Population was all the house hold of freshwater fish farmers in Rao Selatan district Pasaman Region totaling 1,248 households. Samples were taken with a proportional random sampling with a proportion of 10%, so that the respondent amounted to 129 households. Collecting data using guided inquiry, statistical analysis used was descriptive using percentage formula. Tne results showed as follows ; 1) The land area of 0.75 hectares owned by farmers, average income of Rp 2,000,000 - Rp 2.999.000/harvest time, spending Rp 1.500.000 to Rp 1.999.000/month, dependents 4 people, a side job shop, work at home and use the income to childrens education, 2) Freshwater Fish Farmers in Rao Selatan district Pasaman Region providing staple foods 3 times daily, complementary foods and vegetable side dishes, family clothing needs 2 x year, met at the nearest clothing store, the type of house most permanent and the property it self 3) childrens education is generally located at the elementary, junior high, high school and college, school dropouts average 1 person in l family, where education in the neighborhood, the cost average of Rp 300.000 - Rp 500.000/month, resource costs come from the expense of education itself and 4) place of treatment to health centers, health facilities distance of 250 m - 500 m, the source comes from a family cost family nutrition good condition, dispose of waste in landfills and location of basic sanitation is at home